2021
DOI: 10.1097/md.0000000000027418
|View full text |Cite
|
Sign up to set email alerts
|

Has COVID-19 changed the approach to HIV diagnosis?

Abstract: The occurrence of COVID-19 pandemic had a significant negative effect on health care systems over the last year. Health care providers were forced to focus mainly on COVID-19 patients, neglecting in many cases equally important diseases, both acute and chronic. Therefore, also screening and diagnostic strategies for HIV could have been significantly impaired.This retrospective, multicenter, observational study aimed at assessing the number and characteristics of new HIV/AIDS diagnoses during COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…Concerning risk of transmission, we found a decreasing rate of new HIV infections in MSM which was also observed in an Italian cohort during the ongoing COVID-19 pandemic [12]. This could be due to reduced contacts during lockdown as well as the fewer possibilities for testing mentioned earlier, which is more widespread and implemented in this risk group.…”
Section: Discussionsupporting
confidence: 73%
“…Concerning risk of transmission, we found a decreasing rate of new HIV infections in MSM which was also observed in an Italian cohort during the ongoing COVID-19 pandemic [12]. This could be due to reduced contacts during lockdown as well as the fewer possibilities for testing mentioned earlier, which is more widespread and implemented in this risk group.…”
Section: Discussionsupporting
confidence: 73%
“…Due to shifting healthcare restrictions, lockdowns and travel bans worldwide, a large number of migrant populations might not have been able to reach our ED. The impact of the pandemic reducing the number of HIV diagnoses has also been reported by other groups in multiple countries [48–53]. Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention.…”
Section: Discussionsupporting
confidence: 70%
“…Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention. Given the impact of the COVID‐19 pandemic on worldwide detection of HIV in general, we can speculate about an increase in the late diagnosis rate in the coming years, but this has not been reported so far [ 48 , 49 , 50 , 51 , 52 , 53 ]. Despite these limitations, our study demonstrated a robust methodology to generate essential HIV diagnoses and epidemiology data.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that in our study the higher proportion of participants who withdrew because of adverse events may be somewhat related to the COVID-pandemic period during which the study was conducted. It is known how COVID-19 had an important impact on the “HIV world” (involving prevention, diagnosis, and treatment), and it is still also debated whether people with HIV have a poorer prognosis than the general population [ 32 , 33 , 34 ]. The modified lifestyle due to the lockdown curfew, the fear of self-isolation with the feelings of more stress and anxiety may have had a negative impact on the patient’s psychosocial health and may have triggered an increased perception of severe side effects related to the new drug regimen.…”
Section: Discussionmentioning
confidence: 99%